2004
DOI: 10.1140/epjc/s2004-01956-4
|View full text |Cite
|
Sign up to set email alerts
|

Do we understand the single-spin asymmetry for $\pi^0$ inclusive production in pp collisions?

Abstract: The cross section data for π 0 inclusive production in pp collisions is considered in a rather broad kinematic region in energy √ s, Feynman variable x F and transverse momentum p T . The analysis of these data is done in the perturbative QCD framework at the next-to-leading order. We find that they cannot be correctly described in the entire kinematic domain and this leads us to conclude that the single-spin asymmetry, A N for this process, observed several years ago at FNAL by the experiment E704 and the rec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 24 publications
6
68
1
Order By: Relevance
“…This belief is supported by the successful perturbative QCD description of the cross sections for pion production at RHIC, which describes the scattering as the hard scattering of the gluons and quarks in each beam. However, a similar pattern of transverse spin asymmetry is seen at fixed target energy [7], where the measured cross section is considerably higher than the pQCD description [8]. Production by a polarized neutron beam would reverse the roles of the valence u and d quarks in the beam, compared to polarized protons.…”
Section: Polarized Neutrons In Rhic?mentioning
confidence: 62%
“…This belief is supported by the successful perturbative QCD description of the cross sections for pion production at RHIC, which describes the scattering as the hard scattering of the gluons and quarks in each beam. However, a similar pattern of transverse spin asymmetry is seen at fixed target energy [7], where the measured cross section is considerably higher than the pQCD description [8]. Production by a polarized neutron beam would reverse the roles of the valence u and d quarks in the beam, compared to polarized protons.…”
Section: Polarized Neutrons In Rhic?mentioning
confidence: 62%
“…These latter processes are akin to hadroproduction from proton+proton (p+p) collisions such as those at RHIC or at the LHC, where the partons from the incoming beam interact with the target(beam) partons. Measurements of hadron production proceeding from p+p data have been compared to pQCD calculations at different √ s ranges [3]. Results of these comparisons have shown that the pQCD calculations have not correctly described hadron production at decreasing √ s. Only high √ s seemed to be properly described by these models.…”
Section: Hadron Cross-sections At √ S = 17 Gevmentioning
confidence: 99%
“…It was pointed out recently [5] that the standard collinear approach is not able to describe very forward production of π 0 . In Fig.1 Clearly, the standard collinear approach fails badly in the very forward region.…”
Section: From Partons To Hadronsmentioning
confidence: 99%